Sodium lignosulfonate improves shoot growth of Oryza sativa via enhancement of photosynthetic activity and reduced accumulation of reactive oxygen species - Kok, Andrew De-Xian; Wan Abdullah, Wan Muhamad Asrul Nizam; Tang, Chu-Nie; Low, Lee-Yoon; Yuswan, Mohd Hafis; Ong, Janna Abdullah; Tan, Ngai Paing; Lai, Kok-Song (Nature Publishing Group, 2021)
Lignosulfonate (LS) is a by-product obtained during sulfite pulping process and is commonly used as a growth enhancer in plant growth. However, the underlying growth promoting mechanism of LS on shoot growth remains largely unknown. Hence, this study was undertaken to determine the potential application of eco-friendly ion-chelated LS complex [sodium LS (NaLS) and calcium LS (CaLS)] to enhance recalcitrant indica rice MR 219 shoot growth and to elucidate its underlying growth promoting mechanisms. In this study, the shoot apex of MR 219 rice was grown on Murashige and Skoog medium supplemented with different ion chelated LS complex (NaLS and CaLS) at 100, 200, 300 and 400 mg/L The NaLS was shown to be a better shoot growth enhancer as compared to CaLS, with optimum concentration of 300 mg/L. Subsequent comparative proteomic analysis revealed an increase of photosynthesis-related proteins [photosystem II (PSII) CP43 reaction center protein, photosystem I (PSI) iron-sulfur center, PSII CP47 reaction center protein, PSII protein D1], ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), carbohydrate metabolism-related proteins (glyceraldehyde-3-phosphate dehydrogenase 3, fructose-bisphosphate aldolase) and stress regulator proteins (peptide methionine sulfoxide reductase A4, delta-1-pyrroline-5-carboxylate synthase 1) abundance in NaLS-treated rice as compared to the control (MSO). Consistent with proteins detected, a significant increase in biochemical analyses involved in photosynthetic activities, carbohydrate metabolism and protein biosynthesis such as total chlorophyll, rubisco activity, total sugar and total protein contents were observed in NaLS-treated rice. This implies that NaLS plays a role in empowering photosynthesis activities that led to plant growth enhancement. In addition, the increased in abundance of stress regulator proteins were consistent with low levels of peroxidase activity, malondialdehyde content and phenylalanine ammonia lyase activity observed in NaLS-treated rice. These results suggest that NaLS plays a role in modulating cellular homeostasis to provide a conducive cellular environment for plant growth. Taken together, NaLS improved shoot growth of recalcitrant MR 219 rice by upregulation of photosynthetic activities and reduction of ROS accumulation leading to better plant growth.